Automated assignment of modules to lecturers - Kassab, Sarah (2013)
This Dissertation involves modelling the manual process of assigning modules to lecturers as an optimization problem, and presents a software tool which implements this model in order to automate the process of module-lecturer assignment. This is preserved to be helpful as there will be no need to do this process manually which can take a lot of time and efforts especially when there are a lot of modules and lecturers to match. This type of problem is known specifically as the Assignment Problem which is one of the most studied Combinatorial Optimization problems. Optimization solutions often promise finding best solutions in very efficient ways while addressing the problem‟s conditions and main goal. Therefore, the approaches followed in this project are mainly related to studying some of the related optimization problems and their correspondent solutions. Subsequently, a new algorithmic solution is proposed in this dissertation document inspired by the knowledge gained when studying related optimization problems. Moreover, some software development techniques are applied and explained in this document to help implement the solution found and produce a good quality software tool used for the purpose of assigning modules to lecturers. The integration of an optimization based solution within a software application makes it much easier to solve the problem efficiently while eliminating all the difficulties encountered when solved manually.